Right Inferior Parietal Lobule Activity Is Associated With Handwriting Spontaneous Tempo - Bonzano, Laura; Bisio, Ambra; Pedullà, Ludovico; Brichetto, Giampaolo; Bove, Marco (Frontiers in Neuroscience, 2021)
Handwriting is a complex activity including motor planning and visuo-motor integration and referring to some brain areas identified as “writing centers”. Although temporal features of handwriting are important as spatial ones, at our knowledge, there is no evidence of the description of specific brain areas associated with handwriting tempo. People with multiple sclerosis (PwMS) show handwriting impairments which are mainly referred to the temporal features of the task. Aim of this work was to assess differences in the brain activation pattern elicited by handwriting between PwMS and healthy controls (HC), with the final goal of identifying possible areas specific for handwriting tempo. Subjects were asked to write a sentence at their spontaneous speed. PwMS differed only in temporal handwriting features from HC and showed reduced activation with a subset of the clusters observed in HC. Spearman’s correlation analysis was performed between handwriting temporal parameters and the activity in the brain areas resulting from the contrast analysis HC>PwMS. We found that the right inferior parietal lobule (IPL) negatively correlated with the duration of the sentence indicating that the higher the right IPL activity, the faster the handwriting performance. We propose that the right IPL might be considered a “writing tempo center”.